Ultraviolet irradiation suppresses T cell activation via blocking TCR-mediated ERK and NF-κB signaling pathways - Li-Weber, Min; Krammer, Peter H. (The journal of immunology, 2005)
UV irradiation is carcinogenic and immunosuppressive. Previous studies indicate that UV-mediated alteration of APCs and induction of suppressor T cells play a critical role in UV-induced immune suppression. In this study, we show that UV irradiation can directly (independently of APCs and suppressor T cells) inhibit T cell activation by blocking TCR-mediated phosphorylation of ERK and IκB via overactivation of the p38 and JNK pathways. These events lead to the down-modulation of c-Jun, c-Fos, Egr-1, and NF-κB transcription factors and thereby inhibit production of cytokines, e.g., IL-2, IL-4, IFN-γ, and TNF-α, upon TCR stimulation. We also show that UV irradiation can suppress preactivated T cells, indicating that UV irradiation does not only impair T cell function in response to T cell activation, but can also have systemic effects that influence ongoing immune responses. Thus, our data provide an additional mechanism by which UV irradiation directly suppresses immune responses.